2017
DOI: 10.1007/s12011-017-1034-y
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation Changes the Ion Profile in the Pancreas of Chickens Treated with Cadmium

Abstract: Increasing evidence indicates that selenium (Se) could antagonize metal toxicity, including cadmium (Cd) toxicity. However, the effects of Se on Cd-induced changes in the ion profile in the pancreas of chickens have not been reported. In the present study, 128 Hy-Line brown laying chickens were divided into the control group, Se-treated group, Se/Cd-treated group, and Cd-treated group, and we detected the concentrations of 28 ions in the four groups by inductively coupled plasma mass spectrometry. In the Cd-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the present study, our results demonstrated that splenic cells with Cd treatment displayed typical morphological changes associated with apoptosis, and the frequency of apoptosis was markedly increased. However, Se was reported to have antagonistic effects on Cd toxicity in the immune organs of chicken [ 38 ]. Consistent with these studies, our results suggested that Se may significantly recover the normal structure of splenic cells, reduce the frequency of Cd-induced apoptotic cells, restore spleen function and enhance immune function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, our results demonstrated that splenic cells with Cd treatment displayed typical morphological changes associated with apoptosis, and the frequency of apoptosis was markedly increased. However, Se was reported to have antagonistic effects on Cd toxicity in the immune organs of chicken [ 38 ]. Consistent with these studies, our results suggested that Se may significantly recover the normal structure of splenic cells, reduce the frequency of Cd-induced apoptotic cells, restore spleen function and enhance immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently swollen mitochondria with degenerating or missing cristae were observed, and the expression of caspase 3, caspase 9 and p53 was markedly increased in the Cd-treated group. Previous studies revealed that Se supplements restored the normal structure of splenic cells [ 38 ] and prevented mitochondrial dynamic imbalance [ 53 ]. Our results are consistent with these results and demonstrate that Se suppressed expression of Drp1 and Mff and enhanced expression of Mfn1, Mfn2 and Opa1, consequently restoring mitochondrial dynamics equilibrium in chicken spleens.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that Cd can cause serious myocardial damage by inducing the necroptosis route, while Se could act in the prevention of Cd-induced myocardial damage via the activation of the adiponectin pathway [ 149 ]. In addition, Se supplementation in laying chickens seems to change pancreatic ions and profile decreasing Cd accumulation in chicken pancreas [ 150 ].…”
Section: Effects Of Selenium Supplementation In Chickenmentioning
confidence: 99%
“…The selenium function to protect the renal and hepatic tissues against the toxicity of Cd is a result of lipid peroxidation reduction and increases the activities of antioxidant enzymes in these tissues (Newairy et al 2007). Selenium supplementation increased the essential minerals (Cr, Mn, Zn, and Se) and decreased toxic mineral (Cd, Li, and Pb) contents in kidney tissues of chickens, which were induced by Cd, suggesting that Se may decrease the negative effects of Cd and improve the trace mineral homeostasis in tissues of chickens (Zhang et al 2017a;Bao et al 2018). Dietary supplemental Se (2 mg/kg of feed) was effective in reducing the negative effects of Cd (150 mg/kg of feed for 90 days) on the keel bone whereby it reduced mineralisation in broilers and laying hens (Zhang et al 2017a).…”
Section: Reviewmentioning
confidence: 99%
“…Dietary supplemental Se (2 mg/kg of feed) was effective in reducing the negative effects of Cd (150 mg/kg of feed for 90 days) on the keel bone whereby it reduced mineralisation in broilers and laying hens (Zhang et al 2017a). Moreover, in their experiment with Hy-Line Brown laying chickens, Bao et al (2018) demonstrated that Cd accumulation in pancreas decreased by 48.18% in the Setreated group compared with the control group, and that of the Se/Cd-treated group decreased by 21.90% compared with the Cd-treated group. Additionally, accumulation in ovaries of Hy-Line Brown layers was decreased upon Se treatment by about 12.6% compared to the Cd-treated group (Li et al 2018).…”
Section: Reviewmentioning
confidence: 99%